PENGARUH PENERAPAN DIGITAL MARKETING DAN INOVASI PRODUK KOSMETIK TERHADAP KEPUTUSAN PEMBELIAN PADA PT. ORINDO ALAM AYU CABANG PEKANBARU - Ayuarni, Aslamia; Sutrisna, Endang (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
This research was conducted at PT. Orindo Alam Ayu Pekanbaru Branch is located at Ska Mall, 3A Floor No 24-25 Jl. Soekarno Hatta, Kec. Tampan, Pekanbaru City,Riau. The purpose of this study was to determine the effect of the application of Digital Marketing and Product Innovation on Purchase Decisions at PT. Orindo Alam Ayu Pekanbaru Branch partially and simultaneously. In this research, the method used is quantitative descriptive analysis and SPSS. The population of this study is all consumers who make purchases of Oriflame Cosmetic Products at PT.Orindo Alam Ayu Pekeabaru Branch. In the last year, 2020, there were 95 people.To determine the sample using the census method. Data collection techniques through questionnaires and interviews, types and sources of data using primary and secondary data, measurement collection techniques using a rikert scale.From data analysis which includes validation test, reliability test, simple linear regression analysis, multiple linear regression analysis, determination analysis and significance test with t test (partial) test, and f test (simultaneous). The results of this study indicate that the results of testing the first t-test hypothesis, Digital Marketing on purchasing decisions, namely t count (3.717) > t table (1.6614) meaning that Digital Marketing has a significant effect on purchasing decisions.The second quality of service on purchasing decisions is t count (7.716) > t table (1.6614) meaning that cosmetic product innovation has a significant effect on purchasing decisions. The results of the calculated f test (32,921) > F table 3.10. it means that Digital Marketing and Cosmetic Product Innovation simultaneously affect the Decision at PT. Orindo Alam Ayu Pekanbaru Branch Keywords: Digital Marketing, Cosmetic Product Innovation, PurchaseDecision.